On the steps of cell-to-cell HIV transmission between CD4 T cells - Clotet Bonaventura; Cabrera Cecilia; Massanella Marta; Puigdomènech Isabel; Blanco Julià (Retrovirology, 2009)
Abstract Although cell-to-cell HIV transmission was defined in early 90's, in the last five years, several groups have underscored the relevance of this mode of HIV spread between productively infected and uninfected CD4 T cells by defining the term virological synapse (VS). However, unraveling the molecular mechanisms of this efficient mode of viral spread appears to be more controversial than expected. Different authors have highlighted the role of a classical co-receptor-dependent HIV transmission while others describe a co-receptor-independent mechanism as predominant in VS. By analyzing different cellular models (primary cells and cell lines), we suggest that primary cells are highly sensitive to the physical passage of viral particles across the synapses, a co-receptor-independent phenomenon that we call "HIV transfer". Once viral particles are transferred, they can infect target cells by a co-receptor-dependent mechanism that fits with the classical meaning of "HIV transmission" and that is much more efficient in cell lines. Differences in the ability of primary CD4 T cells and cell lines to support HIV transfer and transmission explain most of the reported controversial data and should be taken into account when analyzing cell-to-cell HIV spread. Moreover, the terms transfer and transmission may be useful to define the events occurring at the VS. Thus, HIV particles would be transferred across synapses, while HIV infection would be transmitted between cells. Chronologically, HIV transfer is an early event occurring immediately after the VS formation, which precedes but does not inevitably lead to transmission, a late event resulting in infection.